University performance and regional development: the case of Russia's North-West - Kotomina, O. V.; Tretiakova, E. A. (Baltic Region, 2024)
The role of universities in regional socio-economic systems is pivotal. However, despite the overall trend of GRP growth, regions of Russia’s Northwestern Federal District underperform on education-related measures. These include the share of education in GRP, the percentage of individuals employed in the education sector and the number of universities and students. These trends pose a substantial challenge to regional development, especially in the context of the fourth industrial revolution and the rise of the knowledge economy. The lack of attention to the education sector may stem from the gross underestimation of its contribution to regional development. By implementing their 'third mission', universities exert influence on the economy, politics and socially responsible industries in their home region. A better understanding of the role of universities in regional development requires a comprehensive evaluation of their performance. This study aims to evaluate the performance of regional universities and examine its impact on regional socio-economic indicators. The paper proposes a methodology for evaluating the performance of regional universities and presents the results of its application in the regions of Russia's Northwestern Federal District. The universities of the Arkhangelsk region and St Petersburg demonstrated the highest performance levels, whilst those of the Leningrad region were the lowest. Correlation analysis showed a significant connection between universities' performance levels and the key socio-economic indicators of regional development. Universities' performance levels vary significantly across Russia's Northwestern regions. The findings may interest researchers studying regional development issues and administrators of universities prioritising the implementation of the third mission. Additionally, the results can inform decisions regarding the advancement of higher education at the regional level within the Northwestern Federal District.